The effect of coenzyme Q10 on the state hemostasis in the blood of old animals in high-altitude conditions - Gulbarchyn Alisherovna Asrankulova; Zhyldyz Akmatovna Makhmudova; Mahira Rysbaevna Mirzaeva; Meerim Taalaibekovna Taalaibekova; Zyinat Samidinovna Boronova; Mairambu Bektemirovna Zhorobekova (E3S Web of Conferences)
In this study, the effect of oral administration of coenzyme Q10 on the blood coagulation system parameters in old rats under low- and high-altitude conditions was investigated. It was found that oral administration of coenzyme Q10 at a dose of 30 mg/kg body weight significantly reduced blood clotting time and improved platelet aggregation parameters in old rats under low- and high-altitude conditions. In particular, a decrease in prothrombin time, prothrombin index, thrombin time and activated partial thromboplastin time, and a decrease in ADP concentration in old rats were observed. Consequently, the obtained results indicate the hypocoagulant effect of coenzyme Q10 in the hemostasis system in old rats.